1997
DOI: 10.1111/j.1521-0391.1997.tb00563.x
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Social Support and Treatment Retention on an Inpatient Addiction Treatment Unit

Abstract: The authors measured perceived social support among patients and their families as a predictor of retention in an inpatient addiction rehabilitation program. After detoxification from all substances of abuse, 66 sequentially admitted inpatients gave demographic and diagnostic information and completed scales of perceived social support from the program and their own families. Scales were completed at 7, 14, and 21 days. A total of 46 subjects completed the 21-day program, and 20 did not. Homeless status, initi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
1
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 16 publications
3
14
1
1
Order By: Relevance
“…The total population also included the dependents who could not be incorporated into the final analysis. The rate of 31% for this study's sample is comparable to the rates reported in American and British studies [1,5,6,16,17,20,21,25] whereas the actual rate of the patient population in detoxification is 56%. This result corresponds indeed to other studies from German-speaking countries [8,19,22,23].…”
Section: Discussionsupporting
confidence: 79%
“…The total population also included the dependents who could not be incorporated into the final analysis. The rate of 31% for this study's sample is comparable to the rates reported in American and British studies [1,5,6,16,17,20,21,25] whereas the actual rate of the patient population in detoxification is 56%. This result corresponds indeed to other studies from German-speaking countries [8,19,22,23].…”
Section: Discussionsupporting
confidence: 79%
“…However, it is important to note that research findings in this area have not been consistent. For example, in a study of patients in an inpatient treatment program, Westreich and colleagues (24) found that patients who reported stronger perceived social support from family were less likely to complete treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have found drug use in one's network (21,22), having a substance using live-in partner and drug using social relationships (23) to be associated with continued drug use among individuals in treatment. With respect to retention, studies have found homelessness, perceived weak social support from one's family (24), and having a drug-free partner to be predictors of remaining in treatment (25).…”
Section: Introductionmentioning
confidence: 99%
“…Evidence has pointed towards a positive relationship between higher levels of substance use, number of different substances used, and dropping out of treatment (Gainey, Wells, Hawkins, & Catalano, 1993;Kleinman et al, 1992;Stark, 1992;Westreich, Heitner, & Cooper, 1997). Recently, Maglione, Chao, and Anglin (2000) compared characteristics of methamphetamine users in residential treatment who completed at least 90 days of treatment versus those who left before 90 days.…”
Section: Substance Use Severitymentioning
confidence: 99%